Efficacy of indomethacin compared with magnesium sulfate in the management of preterm labor in pregnancies less than 32 weeks - Ayoub, Jehad; Ramadan, Lina; Nasra, Ayman (Latakia University Journal -Medical Sciences Series, 2018)
The study was made on a sample of 100 pregnancies with preterm labour whom admitted to Tishreen University Hospital, Lattakia, Department of Obstetrics and Gynecology, during the period of May 2016 until May 2017 - Indomethacin and magnesium sulphate activities were studied for inhibition of preterm labor, the most important side effects during treatment and physical costfor using indomethacin and comparing it with the physical cost for using magnesium sulfate. - The success rate of indomethacin for inhibition of labour during the first 48 hours of treatment (86%) while success rate of magnesium therapy (78%) was the same as the previous period. - The average period of time from the start of treatment until the disappearance of uterine contractions was lower in women treated with indomethacin than in women treated with magnesium sulfate and this difference is important in terms of statistical. - The lowest period of inhibition of labor was 8.4. Days for women who were treated with indomethacin versus 3.8 days for women treated with magnesium sulfate by a statistically significant difference. - The most significant side effects caused by the application of indomethacin and the most frequent is (nausea) by (54%) of the total side effects. - The most important side effects caused by the application of Magnesium sulfate and the most frequent is (flushing ) by (66%) of the total side effects - Indomethacin application by rectal in preterm labour inhibition was found to be less costly than using magnesium sulphate. مقارنة فعالية الإندوميتاسين وسلفات المغنزيوم في تدبير المخاض الباكر للحوامل بعمر حملي أقل من 32 أسبوع أجريت الدراسة على عينة مكونة من 100 حالة من المريضات الحوامل المقبولات بقصة مخاض باكر في قسم التوليد وامراض النساء في مشفى تشرين الجامعي – اللاذقية خلال الفترة الممتدة من أيار 2016 حتى أيار 2017 - تم دراسة فعالية كل من الإندوميتاسين وسلفات المغنزيوم في تثبيط المخاض الباكر ودراسة أهم التأثيرات الجانبية خلال المعالجة ودراسة التكلفة المادية لاستعمال الإندوميتاسين ومقارنتها مع التكلفة المادية لاستعمال سلفات المغنزيوم - بلغت نسبة نجاح الإندوميتاسين في تثبيط المخاض بطريقة (الجرعة) لمدة 48 ساعة الاولى من المعالجة - ( 86% ) بينما كانت نسبة نجاح المعالجة بسلفات المغنزيوم ( 78% ) لنفس المدة السابقة - أن متوسط الفترة الزمنية منذ بدء العلاج حتى زوال التقلصات الرحمية كانت أقل عند السيدات المعالجات بالاندوميتاسين منه عند السيدات المعالجات بسلفات المغنيزيوم وكان هذا الفرق هاما من الناحية الاحصائية . - بلغ متوسط أقل فترة تم فيها تثبيط المخاض 8.4 يوماعند السيدات المعالجات بالاندوميتاسين مقابل 3.8 يوماعند السيدات المعالجات بسلفات المغنيزيوم بفارق احصائي هام . - أهم الآثار الجانبية الناجمة عن تطبيق الإندوميتاسين وأكثرها تواردا (الغثيان) بنسبة (54%) من مجمل الأثار الجانبية . - أهم الآثار الجانبية الناجمة عن تطبيق سلفات المغنزيوم وأكثرها تواردا ( التوهج) بنسبة ( 66% ) من مجمل الأثار الجانبية كما تبين أن تطبيق الإندوميتاسين عن طريق الشرج في تثبيط المخاض الباكر هو أقل تكلفة مادية من استعمال سلفات المغنزيوم.